THERMODYNAMIC PROPERTIES OF CELLULOSE IN AQUEOUS ELECTROLYTE SOLUTIONS AT DIFFERENT TEMPERATURE - S.PUNITHA,; A.PANNEERSELVAM,; R. UVARANI, (International Journal of Pharma and Bio Sciences, 2013)
Ultrasonic velocity, density and viscosity have been measured in the aqueous solutions of Hydroxy Propyl Methyl Cellulose (HPMC) with Sodium Chloride (NaCl), Calcium Chloride (CaCl2) and Potassium Chloride (KCl) with a view to understand the nature of interaction between the cellulose and electrolytes at different temperatures (303K,313K and 323K). The acoustical parameters such as adiabatic compressibility (β), intermolecular free (length (Lf), internal pressure (πi), acoustic impedance (za) and solvation number (Sn) are calculated. These parameters provide valuable information in understanding the solute-solvent interaction in a polymer cellulose (HPMC) and electrolyte solutions. The velocity decreases suddenly in addition of electrolyte and then increases on further increase of electrolyte concentration at all three temperatures.